The Effectiveness of Google Maps as an eWOM Media in Its Influence on Visit Intention - Shafa’ Annisa Puspasari; Enjelika Enjelika; Sudarmiatin Sudarmiatin (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study discusses consumer behavior in the context of the effectiveness of Google Maps as an eWOM medium in its influence on intention to visit. The main objective of this study is to analyze the factors that influence intention to visit including eWOM. Five informants were interviewed as part of the qualitative research approach, and secondary data was gathered by consulting a variety of literature sources. According to the study's findings, Google Maps can be utilized as a marketing tool. It is anticipated that the study's consequences will shed light on how users interact with data from Google Maps and how companies can maximize the effectiveness of their digital marketing strategies.